(3GdMLGRjGJ ef TYQ GdTQja GdQVjs - (3CHhGdMSf eMeO Hf GdMSjf Hf ehSi GdQVhj GdYdhj GdMSjfj GdehShjs; (3GdTQja GdQVj , CHh GdMSf eMeO Hf GdMSjf Hf ehSi GdQVj GdYdhj GdMSjfj GdehShj, CHh GdMSf,J (B406 (3g` s
(3ChdgG (B:s
(3hjHOC Hbhdg(B: (3hbGd CjVkG(B: (3hTeeoJ aj Wad GdYTjI faMI MHSJ HQGeI UMHJj hQcGHj s
(3BNQgG (B:s
(3CdG djJ dj ef eGA jHQjf TQHI CdP dbdHj ef ZQjV dHGf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B153 - (3U(B182s
(3GdfSNI HgG MhGTs
(3HGdfSNI JbOje hJCNjQs
(3fSNI KGfjIs
(3HgG TQhM hJYdjbGJ cKjQI s
(3hbO ocJH Ydi GdHWGbI GdeUhQI eY GdcJGH CfgG GdMLGRjGJ ddCHjhQOj hHeQGLYJgG JHjf CfgG MLGRjGJ GdTQja GdQVj s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs